ENDODONTIC TREATMENT OF MANDIBULAR INCISORS WITH AN ATYPICAL ANATOMY - Bogdan Mihai Gălbinaşu; G. Tulus; I. Pătraşcu; L.M. Nica (Amaltea Medical Publishing House, 2018)
Related to endodontic literature, mandibular incisors seem to be infrequently treated from an endodontic point of view, excepting third molars. The low percentage of endodontically treated mandibular incisors can be related to many causes, such as: low prosthetic value, difficult endodontic approach and, a more or less, good endodontic predictability due to intracanalar morphology.